2022
DOI: 10.1136/neurintsurg-2022-018723
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy for acute ischemic stroke in COVID-19 patients: multicenter experience in 111 cases

Abstract: BackgroundData on the frequency and outcome of mechanical thrombectomy (MT) for large vessel occlusion (LVO) in patients with COVID-19 is limited. Addressing this subject, we report our multicenter experience.MethodsA retrospective cohort study was performed of consecutive acute stroke patients with COVID-19 infection treated with MT at 26 tertiary care centers between January 2020 and November 2021. Baseline demographics, angiographic outcome and clinical outcome evaluated by the modified Rankin Scale (mRS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…A multicentre study collected data on 93 COVID-19 LVO patients who eventually underwent MT, and noted a 29% 30-day mortality, which was concurrent with higher inflammatory serum biomarker levels (aspartate, LDH) [ 117 ]. Poor prognosis, with a median NIHSS = 13 at discharge, and high rates of mortality (30.6% by discharge) were also consistently detected in another cohort of 111 LVO patients [ 118 ]. Treatment in the multicentre study by Abdalkader et al and the observational study by Hameed et al most commonly consisted of systemic anticoagulation administration of low-molecular-weight heparin (LMWH) or unfractionated heparin, for CVST.…”
Section: Management Of Patients With Cerebrovascular Sequelae During ...mentioning
confidence: 88%
“…A multicentre study collected data on 93 COVID-19 LVO patients who eventually underwent MT, and noted a 29% 30-day mortality, which was concurrent with higher inflammatory serum biomarker levels (aspartate, LDH) [ 117 ]. Poor prognosis, with a median NIHSS = 13 at discharge, and high rates of mortality (30.6% by discharge) were also consistently detected in another cohort of 111 LVO patients [ 118 ]. Treatment in the multicentre study by Abdalkader et al and the observational study by Hameed et al most commonly consisted of systemic anticoagulation administration of low-molecular-weight heparin (LMWH) or unfractionated heparin, for CVST.…”
Section: Management Of Patients With Cerebrovascular Sequelae During ...mentioning
confidence: 88%
“…http://jnis.bmj.com/ with COVID-19 and may explain why this stroke type is more common. 22 However, it is not well understood why patients with COVID-19 have more strokes, and this is a current area of active study. 23 In patients undergoing MT for LVO, the observed inpatient mortality rate was 22.4%, which appears comparable to the rates in the available literature.…”
Section: Relation To Other Studiesmentioning
confidence: 99%
“… 1 , 2 In addition, recent studies of large series of patients with COVID‐19 infection have reported a devastating clinical outcome of patients with AIS attributable to large‐vessel occlusion treated with mechanical thrombectomy (MT), with mortality rates up to 31%. 3 , 4 …”
mentioning
confidence: 99%